2003
DOI: 10.1016/s0014-5793(03)00155-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three novel Smad binding proteins involved in cell polarity

Abstract: A yeast two-hybrid screen was utilized to identify novel Smad 3 binding proteins expressed in developing mouse orofacial tissue. Three proteins (Erbin, Par-3, and Dishevelled) were identified that share several similar structural and functional characteristics. Each contains at least one PDZ domain and all have been demonstrated to play a role in the establishment and maintenance of cell polarity. In GST (glutathione S-transferase) pull-down assays, Erbin, Par-3, and Dishevelled bound strongly to the isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 45 publications
4
35
1
1
Order By: Relevance
“…Since PAR3, PAR6 and aPKC complex with pSMAD5/8 in a BMP-dependent manner, pSMAD5/8 must also be associated with apical junctions when the cell receives BMP signaling (Fig. 8A) (Warner et al, 2003). In the absence of canonical BMP signaling, the phosphorylation of SMAD proteins is severely attenuated, reducing interactions with the apical polarity complex (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since PAR3, PAR6 and aPKC complex with pSMAD5/8 in a BMP-dependent manner, pSMAD5/8 must also be associated with apical junctions when the cell receives BMP signaling (Fig. 8A) (Warner et al, 2003). In the absence of canonical BMP signaling, the phosphorylation of SMAD proteins is severely attenuated, reducing interactions with the apical polarity complex (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ERBIN has been implicated in TGFb signalling through its interaction with both non-phosphorylated and phosphorylated SMAD2/3 (Warner et al, 2003;Dai et al, 2007). ERBIN overexpression inhibited TGFb-dependent transcription, whereas siRNA against ERBIN stimulated ligand-induced responses.…”
Section: Discussionmentioning
confidence: 99%
“…4) and found that a 25-amino-acid domain (amino acids 1241-1265) of ERBIN is responsible for the interaction with SARA. Because these 25 amino acids were included in a longer 110-amino-acid stretch (1172-1282) that has been shown to interact with SMAD2/3 (Warner et al, 2003;Dai et al, 2007), we further defined the interaction domain of SMAD2 and SMAD3 on ERBIN. Much to our surprise, the SMAD2 and SARA-interacting domains of ERBIN were identical, being contained between amino acids 1241 and 1265.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Des travaux récents ont démontré l'implication de Erbin dans la régulation négative de la voie Ras-MAPK activée par ErbB2 en interagissant avec la forme activée de Ras [26]. Erbin interagit également avec les protéines Smad, maillons incontournables de la signalisation du TGFβR impliqué dans la transition épithéliale-mésenchyme [27]. Erbin n'est pas seulement impliquée dans des réseaux moléculaires de signalisation, mais est également au coeur d'intéressants complexes protéiques participant à l'adhérence cellulaire.…”
Section: Le Tissu éPithélial: Un Système Cellulaire Polariséunclassified